Auditory discomfort in visually sensitive individuals - Haigh, Sarah M.; Haugland, Anna M.; Mendoza, Lourdes R.; Montero, Mackenzie (Frontiers in Psychology, 2023)
Introduction Sensory discomfort occurs in clinical and non-clinical populations. While some of the parameters that evoke visual discomfort have been identified, the parameters of sounds that evoke auditory discomfort are largely unknown. Methods We presented various sounds and asked participants to rate the discomfort they experienced. In Experiments 1 and 2 tones were presented at frequencies between 0.25-8 kHz and modulated sinusoidally in amplitude at frequencies between 0-32 Hz. In Experiment 3 tones were swept in frequency from 500 Hz-2 kHz at sweep rates of 5-50 per second. In Experiment 4, sweeps varied in frequency range and central frequency. Results Discomfort increased with frequency. The effects of the amplitude modulation and sweep rate on discomfort were relatively small and were experienced mainly at low modulation frequencies and high sweep rates. Individuals who experienced visuo-perceptual distortions in the Pattern Glare (PG) Test reported greater auditory discomfort. Discussion This suggests that sensory sensitivity in one modality may occur in another.